Investigations into the determination of hydroxylamine in viscosity-stabilised natural rubber - Crafts R C; Davey J E (Journal of Natural Rubber Research, 1996)
The current method for the determination of hydroxylamine in viscosity stabilised (CV) rubber relies on the use of 0.75 M sulphuric acid as the extractant. This work demonstrates that equally complete extraction can be accomplished using much milder extraction conditions. As ion chromatographic method for determining hydroxylamine has been developed and found to give results comparable to the established UV colorimetric method. The new chromotographic procedure has been used to clarify the concept of free hydroxylamine and to test whether the established colorimetric procedure was, indeed, determining free hydroxylamine. The opportunity has also been taken to establish whether the newer grades of CV rubber now being produced have free and measurable hydroxylamine levels comparable with those of the established gades. Preliminary attempts to extend the work to vulcanised compounds are also described.
Keywords: Hydroxylamine; Viscosity-stabilised natural rubber